Catalytic applications of layered double hydroxides: recent advances and perspectives - Fan, Guoli; Li, Feng; Evans, David G; Duan, Xue (Chemical Society reviews, 2014)
This review surveys recent advances in the applications of layered double hydroxides (LDHs) in heterogeneous catalysis. By virtue of the flexible tunability and uniform distribution of metal cations in the brucite-like layers and the facile exchangeability of intercalated anions, LDHs-both as directly prepared or after thermal treatment and/or reduction-have found many applications as stable and recyclable heterogeneous catalysts or catalyst supports for a variety of reactions with high industrial and academic importance. A major challenge in this rapidly growing field is to simultaneously improve the activity, selectivity and stability of these LDH-based materials by developing ways of tailoring the electronic structure of the catalysts and supports. Therefore, this Review article is mainly focused on the most recent developments in smart design strategies for LDH materials and the potential catalytic applications of the resulting materials. This review article presents the most recent developments in the use of layered double hydroxide materials for catalytic applications.